Dynamic impact simulation tests of deep roadways affected by high stress and fault slip - Qi Wang; Yuncai Wang; Zhenhua Jiang; Hongpu Kang; Chong Zhang; Bei Jiang (International Journal of Mining Science and Technology)
As coal mining depth increases, the combined effects of high stress, mining stress, and fault structures make dynamic impact hazards more frequent. The reproduction of dynamic impact phenomena is basis for studying their occurrence patterns and control mechanisms. Physical simulation test represents an efficacious methodology. However, there is currently a lack of simulation devices that can effectively simulate two types of dynamic impact phenomena, including high stress and fault slip dynamic impact. To solve aforementioned issues, the physical simulation test system for dynamic impact in deep roadways developed by authors is employed to carry out comparative tests of high stress and fault slip dynamic impact. The phenomena of high stress and fault slip dynamic impact are reproduced successfully. A comparative analysis is conducted on dynamic phenomena, stress evolution, roadway deformation, and support force. The high stress dynamic impact roadway instability mode, which is characterized by the release of high energy accompanied by symmetric damage, and the fault slip dynamic impact roadway instability mode, which is characterized by the propagation of unilateral stress waves accompanied by asymmetric damage, are clarified. On the basis, the differentiated control concepts for different types of dynamic impact in deep roadways are proposed.